Worm gets a job - Caple, Kathy (Cambridge, Mass. : Candlewick Press, 2004)
Worm attempts various jobs for his animal friends so that he can buy painting supplies and enter the art contest.
A Junior Library Guild selection.
Keywords: Caricatures and cartoons; Painting -- Fiction; Contests -- Fiction; Money-making projects for children -- Fiction; Worms -- Fiction; Animals -- Fiction; Painting -- Juvenile fiction; Contests -- Juvenile fiction; Money-making projects for children -- Juvenile fiction; Worms -- Juvenile fiction; Animals -- Juvenile fiction